The MDM2–p53–pyruvate carboxylase signalling axis couples mitochondrial metabolism to glucose-stimulated insulin secretion in pancreatic β-cells - Xiaomu Li (Nature Portfolio, 2016)
Mice lacking the tumour suppressor p53 are partially protected from developing diabetes. Here the authors show that p53 is upregulated in the pancreas of diabetic mice where it impairs β cell function by repressing expression of mitochondrial pyruvate carboxylase, thereby inhibiting insulin secretion.